Who will cast the first stone - Sumar, Sabiha; Jamal, Ahmed A. (Cinema Guild, 1988)
A documentary look at the impact of Islamization on women in Pakistan, showing the oppression and injustice which led Pakistani women to the forefront of the political struggle for equal rights.